Ulcerative white spot disease prevalence in the Bolinao-Anda reef complex, the associated bacteria in diseased cora (Porites cylindrica), and disease recovery - Pueblos, Miahnie Joy J. (The Marine Science Institute, College of Science, University of the Philippines Diliman, 2013)
Ulcerative White Spot (UWS) disease prevalence was investigated in the Bolinao-Anda Reef Complex. Five reef were surveyed using 100 x 2 m belt transect totaling to a survey area of 3,000 m2 on April, October 2008 and April 2012.The highest prevalence was observed in sites most distant from the fish cages, particularly the reef neares to Malilnep channel. However, between 2008 and 2012, prevalence was observed to decrease on the aforementioned reef, suggesting affected corals can recover from the disease.Investigations on mucus from Porites cylindrica, one of the coral species affected by UWS, showed that the fluid component of the mucus was capable of regulating the growth of one of the pathogens of UWS (viz., vibrio sp.), and the growth of beneficial bacteria or the expression of pigment-producing genes in violet-pigmented bacterial isolates. This study revealed that the epizootiology of ulcerative white spot disease was not limited to mariculture activities, and that visual symptoms may not necessarily show difference in simple measures of microbial densities and activities between healthy, diseased and recovered corals.